The Effect of Micronized Lignocelluloses on Calcium Metabolism, Egg Shell Quality and Performance of Hy-Line W-36 Laying Hens - Hassani Farahani, Reza; Mehri, Morteza; Ghalyanchi Langeroudi, Arash; Khodayari , Moein (Journal of Poultry Sciences and Avian Diseases, 2024)
Carbohydrates are the main macromolecule of poultry feed (40-70 %), categorized into digestible and indigestible forms. Poultry uses digestible carbohydrates to supply energy. Still, the indigestible part (water-soluble and non-soluble) has different roles in anatomy, histology, water loss, bacterial microflora, mucosal health, normal secretions, feed transport time, and digestion rate in the gastrointestinal tract. Cereals (like corn), the carbohydrate source in poultry feed, can contain mycotoxins or water-soluble indigestible fibers, thus there are some mycotoxin-free commercial products containing insoluble indigestible carbohydrates. This study evaluates the effect of micronized Lignocelluloses (Under trade name ARBOCEL®) on calcium metabolism, eggshell quality, and performance of commercial Hy-Line W-36 layers. The results showed that the product had a good effect on the evaluated factors, but in some cases, it was not meaningful in contrast to other groups. However, it is better to evaluate the impact of using this product in various concentrations, ages, periods, heat-stress conditions, and digestive tract microflora disturbance, which is beyond the scope of this study and can be subject to subsequent works.